Rate and causes of inappropriate stays and the resulting financial burden in a single specialty burns hospital - Nasrin Moradi; Kianoosh Moradi; Rafat Bagherzadeh; Aidin Aryankhesal (BMC, 2022)
Abstract Background One of the most important challenges facing hospitals is inappropriate admissions and stays the reduction of which can contribute to a decline in healthcare costs without reducing the quality of services. The aim of this study was to estimate the rate and causes of inappropriate stays and their financial burden in a single specialty burns hospital. Methods This is mixed methods study conducted in 2021. In the quantitative phase, all medical records of patients admitted to a burn hospital were reviewed and 260 cases were randomly selected. The records were evaluated based on the Appropriateness Evaluation Protocol to estimate the rate and preliminary causes of inappropriate stays and their direct costs. Frequencies and logistic regression were used for the rates and the influential factors in causing inappropriate stay, respectively. In the qualitative phase, 13 senior and middle managers of the hospital were interviewed for their interpretation of the quantitative data and the main causes of inappropriate stays. Qualitative data were analyzed by using Graneheim-Lundman method. Results About 28.5% of the patients had at least 1 day of inappropriate stay and about 6% of the total hospitalization days were inappropriate. Marital status, insurance status, and the length of stay were significantly associated with inappropriate admission (p < 0.05). In addition, the annual inappropriate admission days and the direct cost imposed on the patients were estimated at 1490 days and $ 66,848.17. The main causes of inappropriate stays are categorized under themes of healthcare providers, service recipients, financial issues, extra-organizational features, and equipment. Conclusion A significant percentage of patients experience inappropriate admissions. The number of inappropriate stays, which imposes a high cost on patients, can be reduced by considering the standard criteria for appropriate admissions. In addition, hospital officials can prevent inappropriate stays as much as possible and reduce the costs and increase the productivity of hospitals through proper management and planning as well as a regular monitoring of physicians and patients.